A novel polygonal ring rolling method. (November 2020) - Han, Xinghui; Hua, Lin; Yang, Siwei
Graphical abstract: Highlights: A novel polygonal ring rolling method was proposed. Four typical feeding tool paths are designed and optimized. Plastic deformation modes and geometry evolutions of polygonal ring were revealed. Proposed polygonal ring rolling method is proved to be feasible. Abstract: Polygonal rings are widely applied to fabricate critical ring components, such as cabin of aerospace equipment and large nuts. The traditional ring rolling method is difficult to fabricate polygonal rings owing to their non-rotary geometry characteristics. This paper proposes a novel polygonal ring rolling method using a simple rotary plain ring as the ring workpiece. Firstly, the motivations and principles of polygonal ring rolling method are proposed. Then, four typical feeding tool paths are designed and the plastic deformation modes and geometry evolutions of polygonal ring under these four feeding tool paths are revealed. Meanwhile, four typical feeding tool paths are optimized based on the stability of the polygonal ring rolling process. Finally, the polygonal ring rolling experiments are carried out and it is demonstrated that the proposed polygonal ring rolling method is feasible.